2013
DOI: 10.1016/j.jaapos.2012.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Functional magnetic resonance imaging of horizontal rectus muscles in esotropia

Abstract: PURPOSE Monkey neurophysiology suggests that changes in neural drive rather than extraocular muscle structure underlie sensory-induced strabismus. If this is true, then extraocular muscle structure should be normal. We used magnetic resonance imaging to measure horizontal rectus muscle size and contractility to determine whether muscle structure is a factor in human concomitant esotropia. METHODS High-resolution, quasicoronal plane magnetic resonance imaging was performed in target-controlled central gaze, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 29 publications
1
20
2
Order By: Relevance
“…When the monkeys were examined a few weeks later, it was found that the muscle that had been surgically repositioned had added sarcomeres, implying that the resting length of the muscle had changed to account for the muscle stretch and restricted motility imposed upon it by surgery (Scott 1994). Other studies have documented ( a ) hypertrophic or hypotrophic muscles and mislocalization of muscle pulleys in some forms of human strabismus, ( b ) increases in satellite cell activity in rabbit EOM following resection, ( c ) alterations in neuromuscular junction density following treatment of EOM with botulinum toxin, and ( d ) changes in muscle fiber characteristics and neuromuscular junction density in patients with nystagmus, all of which suggest that muscle remodeling can influence the final state of strabismus and eye movement disruption (Berg et al 2012, Christiansen & McLoon 2006, Harrison et al 2007, Oh et al 2002, Schoeff et al 2013). However, an examination of the EOM in monkeys with prism-reared strabismus and no prior surgical treatment found no gross changes in muscle or muscle pulleys (Narasimhan et al 2007), although cellular characteristics of the muscle and contractility were not measured.…”
Section: What Factors Govern Eye Misalignment and Disruption Of Eymentioning
confidence: 99%
“…When the monkeys were examined a few weeks later, it was found that the muscle that had been surgically repositioned had added sarcomeres, implying that the resting length of the muscle had changed to account for the muscle stretch and restricted motility imposed upon it by surgery (Scott 1994). Other studies have documented ( a ) hypertrophic or hypotrophic muscles and mislocalization of muscle pulleys in some forms of human strabismus, ( b ) increases in satellite cell activity in rabbit EOM following resection, ( c ) alterations in neuromuscular junction density following treatment of EOM with botulinum toxin, and ( d ) changes in muscle fiber characteristics and neuromuscular junction density in patients with nystagmus, all of which suggest that muscle remodeling can influence the final state of strabismus and eye movement disruption (Berg et al 2012, Christiansen & McLoon 2006, Harrison et al 2007, Oh et al 2002, Schoeff et al 2013). However, an examination of the EOM in monkeys with prism-reared strabismus and no prior surgical treatment found no gross changes in muscle or muscle pulleys (Narasimhan et al 2007), although cellular characteristics of the muscle and contractility were not measured.…”
Section: What Factors Govern Eye Misalignment and Disruption Of Eymentioning
confidence: 99%
“…16, 17 MRI in humans with concomitant ET shows that the MR is larger than normal, but the LR is not subnormal. This suggests that human concomitant ET is associated with peripheral EOM abnormality, 18 yet it remains mysterious how abnormal sized EOMs could be commanded by normal motor unit behavior to execute normal eye movements, and remains uncertain if abnormal EOM size is cause or effect of strabismus. Changes in EOM length do not explain strabismus.…”
mentioning
confidence: 99%
“…Schoeff and colleagues 11 noted supernormal volume of the medial rectus muscle and a trend to enlargement of the lateral rectus muscle in patients with esotropia. Generalized hypertrophy may be related to abnormal discharge patterns of motor neurons innervating the extraocular muscles previously demonstrated in monkeys with DSC and is consistent with similar changes in both agonist and antagonist muscles in experimentally induced strabismus in monkeys.…”
Section: Discussionmentioning
confidence: 98%
“…Although 4 patients in the current study had undergone previous strabismus surgery for esotropia and DVD, prior strabismus surgery cannot explain this finding: it has been elsewhere demonstrated that strabismus surgery does not alter extraocular muscle volume or maximum cross section. 11 Recession of a muscle does not remove tissues and has a negligible effect on volume. 11 Whatever effect previous strabismus surgery might have had on the muscles studied here, it could not have directly produced the observed size increases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation